Genetic Diversity of the Structure of HSP70 Gene in Kampung Unggul Balitbangtan (KUB), Walik, and Kate Walik Chickens - A. Aryani; D. D. Solihin; C. Sumantri; R. Afnan; T. Sartika (Tropical Animal Science Journal, 2019)
Our research was designed to identify the sequence variations of heat shock protein 70 (HSP70) gene in three breeds of native Indonesian chickens, Kampung Unggul Balitbangtan (KUB) chicken, Walik chicken, and Kate Walik chicken. Total DNA was isolated from the whole blood using a DNeasy blood and tissue kit. The HSP70 gene was amplified and sequenced from 94 chickens using PCR. The amplification product was 787 bp long, consisting of a 210 bp promoter region, a 112 bp long 5′untranslated region (UTR), and a 465 bp protein coding region. Our KUB, Walik, and Kate Walik chicken HSP70 gene sequence alignments express genetic diversity in the promoter region (insertions and deletions), 5′UTR (deletions and nucleotide substitutions), and at the beginning of the coding region (nucleotide substitutions). Four haplotypes, H1, H2, H3, and H4, were identified in the HSP70 gene protein coding region. The haplotype H2 was found in all three chickens, while H4 was only found in Walik chicken. The H4 is a novel haplotype which never reported before. Based on a median-joining network analysis, H4 is a haplotype produced by mutations at two specific sites (g.370A>G and g.388C>G) in the protein coding region of the HSP70 gene of the chicken. It could be concluded that Walik chicken can be used as a standard for heat stress genotyping in Indonesian local chickens, because it has complete HSP70 gene haplotypes.